2016
DOI: 10.1186/s12348-016-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant proliferative vitreoretinopathy in syphilitic uveitis

Abstract: BackgroundSyphilis is a reemerging sexually transmitted disease that can lead to any type of intraocular inflammation. Prognosis of syphilitic uveitis after appropriate therapy is classically regarded as favorable. However, visual threatening complications may develop, rarely including rhegmatogenous/tractional retinal detachment (R/T RD) and proliferative vitreoretinopathy.FindingsWe report 4 patients presenting with complex R/T RD and fulminant proliferative vitreoretinopathy despite treatment among 19 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Among them can be seen cases like this one in which vitreous surgery was effective for proliferative changes from the obstructive retinal vasculitis. Queiroz et al [ 10 ] reported 4 cases in which proliferative retinopathy developed in the early stages following syphilis treatment and for which vitreous surgery was performed, and they identified a high rate of retinal necrotic change. Haug et al [ 11 ] report 11 cases of rhegmatogenous retinal detachment complicated with syphilitic uveitis, theorizing that retinal necrosis caused by the syphilis was the origin of the tear formation.…”
Section: Discussionmentioning
confidence: 99%
“…Among them can be seen cases like this one in which vitreous surgery was effective for proliferative changes from the obstructive retinal vasculitis. Queiroz et al [ 10 ] reported 4 cases in which proliferative retinopathy developed in the early stages following syphilis treatment and for which vitreous surgery was performed, and they identified a high rate of retinal necrotic change. Haug et al [ 11 ] report 11 cases of rhegmatogenous retinal detachment complicated with syphilitic uveitis, theorizing that retinal necrosis caused by the syphilis was the origin of the tear formation.…”
Section: Discussionmentioning
confidence: 99%
“…Visual prognosis in syphilitic uveitis is classically considered as favourable, with good response to adequate antibiotic therapy, 46,74,83,84 even though complications are not uncommon and poor outcome may be seen in a significant number of cases. 37,44,85 HIV coinfection is not associated with a worse visual outcome. 42,75,76,84,86 However, posterior segment complications and incidence rates of visual acuity loss, but not rates of vision loss and changes in visual acuity, are slightly more common among those with HIV infection.…”
Section: Prognosismentioning
confidence: 91%
“…The authors could find that baseline BCVA and initial improvement at 1 week were associated with recovery at 1 month and periocular dexamethasone injections and methylprednisolone pulses negatively affected the outcomes. However, complications might still arise after 1 month of treatment onset, as previously reported [26].…”
Section: Discussionmentioning
confidence: 63%